Determination of Parent and Oxygenated Polycyclic Aromatic Hydrocarbons (PAHs) in Waste Cooking Oil and Oil Deodorizer Distillate by GC–QQQ–MS. (3rd December 2019) - Teng, Chong; Wu, Shimin; Sun, Yaqing; Gong, Guangyi
Abstract: Background: Polycyclic aromatic hydrocarbons (PAHs) and oxygenated PAHs (OPAHs) are classes of contaminants that are present in the environment and food. They pose a great threat to human health because of their carcinogenicity and mutagenicity. Very few studies have focused on their concentration in waste cooking oil (WCO) and oil deodorizer distillate (ODD). Objective: This study aimed ( 1 ) to design a reliable method to determine 16 PAHs and 4 OPAHs in both WCO and ODD and ( 2 ) to determine and analyze PAH and OPAH concentrations in actual samples to provide references for further research. Method: The PAH determination approach included double liquid–liquid extraction, double solid-phase extraction, and GC–triple quadrupole tandem MS determination. Oxidation indices were determined by titrimetry. Results: The method reached good linearity ( R 2 > 0.99) and an acceptable recovery rate (55.01–126.16% for WCO and 57.48–128.97% for ODD). Ten WCO and five ODD samples were determined, and the total concentration of 16 PAHs varied from 16.34 to 239.01 and 101.08 to 198.04 μg/kg in WCO and ODD, respectively. Among the 16 PAHs, three-ring PAHs typically contributed the most. It was also found that the acid value has a strong correlation with the concentration of OPAHs, probably because of the contribution of free fatty acids to OPAH formation. Conclusions: The proposed method was effective in the analysis of PAHs and OPAHs in WCO and ODD.